Pengembangan Multimedia Pembelajaran Menggunakan Google Sites Berbasis Kearifan Lokal Rumah Knock Down Tanjung Batu Bagi Siswa SMA - Pramesti, Rachma Puspita Sulistianing; Sugiarti, Sugiarti; Lia, Linda (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The aim of this research is to create valid, practical and effective learning media for high schools using Google Sites based on the local wisdom of Rumah Knock Down. This research was designed using the development research (DR) method, Rowntree’s development model, which consists of three stages: planning, development, and evaluation. For the evaluation stage, the Tessmer formative was used, which consists of five stages: personal evaluation, expert evaluation, one-on-one meetings, small groups, and field tests. The research results at the expert evaluation stage reached 3.7 in the medium category, at the one-on-one meeting stage it was 91 percent in the very practical category, at the small group stage it was 85 percent in the very practical category, and at the field test stage it was 0,54 with very medium category. As a result of using physics learning media based on the local wisdom of the Knock Down Tanjung Batu house for high school students, the learning results show that this media is suitable for use.